Effect of soy products and isoflavones on oxidative stress parameters: A systematic review and meta-analysis of randomized controlled trials. (November 2020) - Morvaridzadeh, Mojgan; Nachvak, Seyed Mostafa; Agah, Shahram; Sepidarkish, Mahdi; Dehghani, Fereshteh; Rahimlou, Mehran; Pizarro, Ana Beatriz; Heshmati, Javad
Graphical abstract: Highlights: Soy products and isoflavones has been widely used as protein source and functional foods. Soy products and isoflavones intake have been shown to exert antioxidant effects. The results of our study show that soy products and isoflavones intake are effective in improving oxidative stress parameters. Abstract: Soy products and isoflavones intake have been shown to exert antioxidant effects. There are several randomized control trials (RCTs) that evaluated the effect of soy products intake on oxidative stress (OS) parameters. The aim of the present systematic review and meta-analysis was to summarize the results of RCTs evaluating the effect of soy products and isoflavones intake on OS parameters. Randomized trials that assessed the effect of soy products and isoflavones intake on OS parameters in adults were identified through searching in electronic databases: Cochrane clinical trial center, Embase, PubMed, Scopus, and Web of Sciences up to April 2020. Random effects model was used to calculate the effects sizes of soy intake on OS parameters. Twenty-four trials with 1, 852 participants were eligible and were included in the meta-analysis which measured OS parameters. Soy intake compared to control group significantly reduced MDA levels (SMD: −0.53; 95% CI: −0.86, −0.19; I 2  = 88.3%), increased GSH levels (SMD: 0.51; 95% CI: 0.13, 0.88; I 2  = 72.4%), SOD activity (SMD: 0.53; 95% CI: 0.08, 0.99; I 2  = 84.1%), TAC (SMD: 0.54; 95% CI: 0.27, 0.82; I 2  = 49.3%) and TRAP (SMD: 1.74; 95% CI: 0.82, 2.65; I 2  = 81.3%) significantly compared to control group. Soy products and isoflavones intake are effective in improving OS parameters in adults compared with controls; thus, it could be a valuable advise to control OS progress in chronic diseases.